Plant Regeneration through Somatic Embryogenesis from Leaf Sheath Derived Callus of Sugarcane (Saccharum officinarum L.) var. Isd -16 - Roy, Mohashweta; Hossain, M.; Biswas, A.; Biswas, M. K.; Islam, R. (Plant Tissue Culture and Biotechnology, 2011)
Leaf sheath explants of an indigenous variety Isd-16 of sugarcane (Saccharum officinarum L.) produced light yellow friable callus after culturing on to MS with 2,4-D (2 - 4 mg/l) and NAA (3 - 5 mg/l) singly. Callus formation was the maximum on MS + 3 mg/l 2,4-D. Callus underwent embryogenesis producing huge number of somatic embryos when subcultured on MS with 15 - 30 mg/l L-proline, 3 mg/l 2,4-D + 5 - 10% coconut water (v/v) and 3 mg/l 2,4-D + 10% CW (v/v) + 300 - 500 mg/l CH. L-proline significantly enhanced somatic embryo-genesis and 25 mg/l L-proline in MS was the best culture medium formulation. Most of the somatic embryos germinated and developed plantlets after 1 - 2 weeks of incubation in proline-supplimented medium. On the other hand, maturation and germination of embryos were achieved on half-strength MS with or without 0.25 - 1.0 mg/l L-proline, and 5% coconut water (v/v). Somatic embryos derived plantlets were then successfully transferred to natural condition through successive phages of acclimation. Key words: Plant regeneration, Leaf sheath, Somatic embryogenesis, Sugarcane D. O. I. 10.3329/ptcb.v21i2.10237 Plant Tissue Cult. & Biotech. 21(2): 143-149, 2011 (December)